2014
DOI: 10.2147/mb.s51328
|View full text |Cite
|
Sign up to set email alerts
|

Egg donation compensation: ethical and legal challenges

Abstract: Nearly 8,000 children were born in the US in 2011 as a result of assisted reproductive technology involving the use of donor oocytes. While this technology has been widely utilized, worldwide numbers are difficult to calculate. The ethics of the process and of payment provided to donors continue to be highly debated. This paper examines international debates about the legality and morality of the use of donor eggs to assist in family development and just recompense of donors. Aside from a nearly universal pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Many countries impose restrictions on oocyte donation, ranging from banning the practice altogether to limiting donor anonymity or compensation (20). These restrictions may reflect a variety of factors, including ongoing debates over the ethics of third-party reproduction (e.g., the potential for harm to children following anonymous oocyte donation, and whether compensation of oocyte donors inappropriately commodifies human genetic material or unduly influences potential oocyte donors) and may motivate non-U.S. resident patients to seek CBRC in the U.S. (20,(22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Many countries impose restrictions on oocyte donation, ranging from banning the practice altogether to limiting donor anonymity or compensation (20). These restrictions may reflect a variety of factors, including ongoing debates over the ethics of third-party reproduction (e.g., the potential for harm to children following anonymous oocyte donation, and whether compensation of oocyte donors inappropriately commodifies human genetic material or unduly influences potential oocyte donors) and may motivate non-U.S. resident patients to seek CBRC in the U.S. (20,(22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
“…Only 2.4% of donors who participated in their study reported donating more than 6 times. 86 Donating twice (42.1%) or once (31.6%) were also the most frequent numbers reported by the 19 donors interviewed by Almeling. 87 In addition to COI, COCs may play an important role during the monitoring stage.…”
Section: Post-stimulation/monitoringmentioning
confidence: 92%
“…The same study finds that among the 80 donors interviewed, almost 20 percent donated solely because of financial need and approximately 60 percent of the sample identified remuneration as very significant in the decision to donate. 21 The vulnerability of potential donors relative to physicians and intended parents raises substantial concerns regarding the absence of strict oversight over the informed consent process, with some questioning the utility of this method altogether. 22 The medical and psychological risks present in oocyte donation, the potentially coercive payment offers, and the vulnerability of those most often targeted by intended parents and egg brokers illustrate the specific interests and needs of donors regarding their health and safety.…”
Section: Medical and Psychological Risksmentioning
confidence: 99%